2017
DOI: 10.1103/physrevlett.119.181303
|View full text |Cite
|
Sign up to set email alerts
|

Dark Matter Detection Using Helium Evaporation and Field Ionization

Abstract: We describe a method for dark matter detection based on the evaporation of helium atoms from a cold surface and their subsequent detection using field ionization. When a dark matter particle scatters off a nucleus of the target material, elementary excitations (phonons or rotons) are produced. Excitations which have an energy greater than the binding energy of helium to the surface can result in the evaporation of helium atoms. We propose to detect these atoms by ionizing them in a strong electric field. Becau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 69 publications
(66 reference statements)
2
79
0
Order By: Relevance
“…Light dark matter may also be detected through its coupling to optical phonons in polar materials [25]. Superfluid 4 He has been previously considered for WIMP detection in [26] as part of the HERON project [27,28], and has recently gained attention in the context of low-mass dark matter detection [29][30][31]. Advantages of superfluid 4 He include a) Low target arXiv:1810.06283v1 [physics.ins-det] 15 Oct 2018 mass, allowing relatively good kinematic matching to low-mass dark matter particles; b) Multiple observable and distinguishable signal channels summing to the total recoil energy, including phonons and rotons (commonly referred to collectively as 'quasiparticles'), substantial scintillation light, and triplet helium excimers; c) Inhibited vibrational coupling of the target mass to the environment (the container walls), due to the distinct superfluid phonon/roton dispersion relation; d) High radiopurity, as helium has no long-lived isotopes, may be purified using getters or cold traps, and impurities freeze out of the bulk; d) A large band gap energy of 19.77 eV (the energy needed to excite atomic helium to an n = 2 state), inhibiting all electronic excitation backgrounds below this energy; e) Quasiparticle excitations which are long-lived and ballistic, thereby preserving recoil information encoded in their production; and f) A liquid state down to zero K, enabling mK-temperature calorimetric readout of an easily-scalable liquid target mass.…”
Section: Introductionmentioning
confidence: 99%
“…Light dark matter may also be detected through its coupling to optical phonons in polar materials [25]. Superfluid 4 He has been previously considered for WIMP detection in [26] as part of the HERON project [27,28], and has recently gained attention in the context of low-mass dark matter detection [29][30][31]. Advantages of superfluid 4 He include a) Low target arXiv:1810.06283v1 [physics.ins-det] 15 Oct 2018 mass, allowing relatively good kinematic matching to low-mass dark matter particles; b) Multiple observable and distinguishable signal channels summing to the total recoil energy, including phonons and rotons (commonly referred to collectively as 'quasiparticles'), substantial scintillation light, and triplet helium excimers; c) Inhibited vibrational coupling of the target mass to the environment (the container walls), due to the distinct superfluid phonon/roton dispersion relation; d) High radiopurity, as helium has no long-lived isotopes, may be purified using getters or cold traps, and impurities freeze out of the bulk; d) A large band gap energy of 19.77 eV (the energy needed to excite atomic helium to an n = 2 state), inhibiting all electronic excitation backgrounds below this energy; e) Quasiparticle excitations which are long-lived and ballistic, thereby preserving recoil information encoded in their production; and f) A liquid state down to zero K, enabling mK-temperature calorimetric readout of an easily-scalable liquid target mass.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has given important information on the properties of this strongly interacting Bose system. In addition, it has been suggested that QE can be used as a probe of other phenomena like the detection of solar neutrinos [3] and of dark matter [4]. Here we propose that QE can be very useful to uncover aspects of Quantum Turbulence (QT).QT [5,6] is a paradigm of turbulence that takes place in a pure superfluid, i.e.…”
mentioning
confidence: 99%
“…The first one is via calorimetric techniques, and it requires the total energy deposited in the system to be larger than 1 meV [42]. The second one instead employs the so-called "quantum evaporation" and requires for the energy of the single excitations to be higher than 0.62 meV [43]. From the action (1) one can compute the rates of emission of one and two phonons [30].…”
Section: Emission Of One and Two Phononsmentioning
confidence: 99%